Achievement Standard Daycare Quality In semarang City District Banyumanik - Inayah, Fadmun Fiqda; Khamidun, Khamidun (BELIA: Early Childhood Education Papers, 2016)
The purpose of this study was to determine the condition of the implementation, management, compliance guidelines, as well as standardized achievement TPA in District Banyumanik,Semarang. The research subjects as much as 3 Child Care in Sub Banyumanik, Semarang. Data analysis with interactive descriptive techniques to the stage of data collection, data reduction, presentation and conclusion. The results of this study are overall achievement standards daycare qualified in District Banyumanik only reached by TPA QBS Islam Hidayatullah, while the achievement standard child development, content standards, standardized processes, standards educators and education personnel, the standard of infrastructure, assessment standards, management standards, as well as finance standards, set by the National Accreditation Board (BAN) is as follows; (1) TPA Silmi obtain the results achievement of quality standards category Good TPA (2) TPA Bina Fitrah Silmi obtain the results achievement of quality standards categories Good TPA, (3) QBS Islam Hidayatullah Silmi get results daycare achievement of quality standards category Very Good